2020
DOI: 10.1097/ncq.0000000000000412
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Electronic Health Records and Machine Learning to Tailor Nursing Care for Patients at High Risk for Readmissions

Abstract: Background: Electronic health record (EHR)-derived data and novel analytics, such as machine learning, offer promising approaches to identify high-risk patients and inform nursing practice. Purpose:The aim was to identify patients at risk for readmissions by applying a machine learning technique, Classification and Regression Tree (CART), to EHR data from our 300-bed hospital. Methods:We conducted a retrospective analysis of 2,165 clinical encounters from August-October 2017 using data from our health system's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…The details of the types of model validation used in each study could be found in Additional supporting file 2 : Supporting Information Table S2. Twenty-one studies (49%) randomly partitioned data into training/testing parts or training/validation/testing parts [ 51 , 53 , 55 , 56 , 58 , 60 , 65 67 , 70 , 73 , 74 , 76 , 78 , 79 , 82 87 ], and most of these studies utilized some form of cross-validation in the training sets for model construction. Thirteen studies (30%) validated using various types of resampling procedures, such as k-fold cross-validation [ 49 , 54 , 57 , 61 , 68 , 69 , 77 , 81 ] (19), stratified k-fold cross-validation [ 61 , 80 ], repeated k-fold cross-validation [ 48 ], and repeated random test-train splits [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…The details of the types of model validation used in each study could be found in Additional supporting file 2 : Supporting Information Table S2. Twenty-one studies (49%) randomly partitioned data into training/testing parts or training/validation/testing parts [ 51 , 53 , 55 , 56 , 58 , 60 , 65 67 , 70 , 73 , 74 , 76 , 78 , 79 , 82 87 ], and most of these studies utilized some form of cross-validation in the training sets for model construction. Thirteen studies (30%) validated using various types of resampling procedures, such as k-fold cross-validation [ 49 , 54 , 57 , 61 , 68 , 69 , 77 , 81 ] (19), stratified k-fold cross-validation [ 61 , 80 ], repeated k-fold cross-validation [ 48 ], and repeated random test-train splits [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…The literature has demonstrated that these methods are useful when managing a large amount of data, as shown in research aimed at identifying critical elements for predicting risk status in nursing documentation [ 32 ]. Another recent study in the nursing field considered MLTs and administrative data to identify patients at high risk for hospital readmission [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…All the analyses were conducted on the de‐identified patient dataset, and patients who were admitted to other hospitals not defined above were not captured. The preprocessed features ( n = 481), including labs, demographics, the number of outpatient visits prior to the current visit, and the number of Emergency Department (ED) visits prior to the current visit, 15,16,38 were extracted from the EHR data using both data‐driven methods and clinical knowledge (Table II). The dataset also included 21 variables extracted according to the LACE 13 and HOSPITAL 14 indices: the length of stay, the number of ED visits in the past six months, the number of (unplanned) hospital admissions in the past year, whether any procedure was performed during the hospitalisation, and 17 ICD‐9/ICD‐10 code groups to calculate the Charlson comorbidity index score in the LACE index.…”
Section: Methodsmentioning
confidence: 99%